DESENVOLVIMENTO DE DISPOSITIVO TÉCNICO PARA AUXILIAR A LACTAÇÃO EM PUÉRPERAS - Abreu, Helena Ritter de (2020)
Introduction: Exclusive breastfeeding in the first six months of life, recommended by the World Health Organization and complemented until the age of two, remains a challenge. Government actions with managerial, educational and assistance technologies witch benefit breastfeeding have positively impacted the prevalence rates of exclusive breastfeeding according to the update of the National Study of Food and Child Nutrition which went from 36.3% to 45.7%, showing that early weaning is a public health problem. Under this focus, the present work has emerged from a local demand and it inserts in the Sustainable Development Goals - Agenda 2030 of the United Nations (UN), more specifically in the Health and Well- Being Objective - Improving maternal health and reducing neonatal mortality. It is also inserted in the Research Priority Agenda of the Ministry of Health Axis 14 - Maternal and Child Health. Purpose: Develop a technical product to assist in the extraction of human milk in puerperal women, in a low-cost, easy-to-handle conventional breastfeeding brassiere form, from a literature review on technical and/or technological products auxiliaries for the extraction of available human milk. Methodology: The development of the technical device has demanded, a priori, a literature review regarding breastfeeding, child health, lactation and study of the anatomophysiology of lactating breast, for the subsequent production of the technical prototype followed by a manual and an explanatory video available on the web through free apps. For literature review on the benefits and safety of using accessory devices for the extraction of human milk, the following question was formed: “what has been produced in the literature that provides evidence of whether or not to use accessory devices to express milk?” A data collection in the virtual libraries was accomplished: VHL, Medline, Scopus, Science Direct and Cochrane, as descriptors “breast feeding” (“lactancia materna”), “extraction of milk” (“breast pumping” “extracción de maternal leche”) and human milk, a time frame of the last 20 years of publication was established. The preparation of the technical product has followed the anatomy of the breast and the recommendations of government agencies regarding the ideal period of breastfeeding. Results: The updated state-of-the-art literature review on technical and/or technological products auxiliary to the expressing of milk and the development of the device wich it is used by the nursing mother in helping to express milk it will avoid early weaning, with the awareness of the greater importance to the act of exclusive breastfeeding in the first six months of life. The developed technical product presents the safety requirements, comfortability, being hypoallergenic, easy to handle, washable and practical to use, adding value to the conventional breastfeeding bra. Final considerations: The description of different auxiliary methods for expressing milk and breast protectors consists in available devices in the trade industry with varying costs. Managerial, educational and assistance technologies aimed at breastfeeding should enhance these auxiliary devices, when necessary, avoiding early weaning. The strengthening of practices which benefit breastfeeding and, when necessary, , the availability at hospital and domestic level of the use of technical and / or technological products auxiliary to milk extraction, favoring breastfeeding, lactation and the protection of the newborn and the puerperal women in their primordial basic needs, ensuring the best for the beginning of the life of the child.